2007
DOI: 10.1017/s0954579407000594
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status mediates the genetic contribution of the dopamine receptor D4 and serotonin transporter linked promoter region repeat polymorphisms to externalization in preadolescence

Abstract: The impact of socioeconomic status (SES) and genetic polymorphisms on individual differences for externalized behaviors have often been investigated separately in studies of children and adults. In a general population sample of 607 Italian preadolescents, we examined the independent and joint effects of SES and the dopamine receptor D4 (DRD4) and serotonin transporter linked promoter region (5-HTTLPR) polymorphisms upon rule-breaking and aggressive behaviors measured with the Child Behavior CheckList/6-18. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 99 publications
(135 reference statements)
4
48
2
1
Order By: Relevance
“…Moreover, there were no significant differences owing to SES (t = -0.72, p = 0.47) or age (t = -1.34, p = 0.18) between PrISMA children belonging to families who agreed versus those belonging to families who did not agree to participate in the genetic study [41].…”
Section: Statistical Analysesmentioning
confidence: 84%
See 3 more Smart Citations
“…Moreover, there were no significant differences owing to SES (t = -0.72, p = 0.47) or age (t = -1.34, p = 0.18) between PrISMA children belonging to families who agreed versus those belonging to families who did not agree to participate in the genetic study [41].…”
Section: Statistical Analysesmentioning
confidence: 84%
“…Previous controls for biases performed upon demographic and behavioural variables showed no, or only modestly significant differences in behavioural variables in children belonging to families who agreed versus those belonging to families who did not agree to participate in the genetic study [41,42]. Moreover, there were no significant differences owing to SES (t = -0.72, p = 0.47) or age (t = -1.34, p = 0.18) between PrISMA children belonging to families who agreed versus those belonging to families who did not agree to participate in the genetic study [41].…”
Section: Statistical Analysesmentioning
confidence: 88%
See 2 more Smart Citations
“…A number of previous studies have detected gene × parenting and gene × SES interactions on externalizing behaviors; however, the direction of these detected interactions have been inconsistent, with some studies reporting that genes play a less important role at higher level of positive parenting (e.g., DiLalla et al, 2009;Feinberg et al, 2007) or higher SES (e.g., Nobile, et al, 2007), while others reported the opposite pattern (e.g., Brody et al, 2009;Leve et al, 2009;Tuvblad et al, 2006). In the following sections, we first review the extant genetic and socialization literatures on externalizing behaviors, and then describe the utility of a gene × environment interaction approach.…”
Section: Introductionmentioning
confidence: 99%